Retroactive Validation of Marriage according to 1983 Code of Canon Law (can. 1161-1165) - Paweł Stasiuk (Kościół i Prawo, 2014)
In the presented study, the author concentrated his attention on the functioning of the institution of a retroactive validation under the Code of 1983. From the conducted analyses it results that retroactive validation in an extraordinary manner of marriage validation, that was contracted in an invalid manner as a result of the existence of a breaching impediment or the lack of a canon form. That does not require the renewed matrimonial consent as a principal condition of the aplication of this institution is the existence of a valid matrimonial consent.